Penyuluhan Capacity Building Penguatan Umkm Kedai Dorokolano Galala Kabupaten Halmahera Barat Maluku Utara Dalam Era New Normal - Prince Charles Heston Runtunuwu; Bakri Soamole (Prisani Cendekia, 2022)
The Covid-19 pandemic has an impact on all levels of society, including people in RT 02 RW 07, Kahuripan Village, Tawang Subdistrict, Tasikmalaya City, some people have experienced a decrease in working hours even losing their jobs, whether they work in restaurants, shops or freelance daily workers. The purpose of this service activity is to increase knowledge about increasing income with entrepreneurship training in the New Normal Era so that this activity is useful for providing entrepreneurial knowledge and skills from making products to marketing to consumers in the New Normal Era. The method used in this service activity is training and mentoring with effective methods to increase the knowledge and skills of the people affected by Covid-19 in making products to market them so that they can increase the income of the community in RT 02 RW 07, Kahurpian Village, Tawang District, Tasikmalaya City. The results achieved from this service activity are increasing knowledge about increasing income from the entrepreneurial sector for people affected by Covid-19, starting from the manufacture of products to the marketing process in order to increase income. This will drive the economy in the region and can further alleviate poverty